Chapter 13 The social organization of (in-)attention - Bergmann, Jörg R. (Taylor & Francis, 2024)
"Attention" is a primordial topic throughout Goffman's work. Already his dissertation thesis (1953) includes a separate chapter on "the organization of attention". In his later studies he developed various concepts related to attention, such as focused/unfocused interaction or "civil inattention". Although attention is evidently a crucial dimension of the interactional order, Goffman did not elaborate this topic systematically. The study of attention was later refined and enriched by conversation analysts who underlined the role of visual displays of attentiveness in social interaction. Against the backdrop of the notion of "focused interaction", this paper examines how the psychological approach to "joint attention" differs from or amplifies Goffman's studies. Based on some of Cartier-Bresson's photos, it is shown that the contrasting set of focused/unfocused interaction needs to be supplemented by a third type of attention order, in which members are collectively oriented to an outward event. After a discussion of some of the practices of sustaining and re-establishing a focus of attention, empirical evidence is provided that certain interactional purposes can be achieved by displaying inattention. In the final discussion of Goffman's concept of "civil inattention", some historical and sociological dimensions are pointed out along which this concept can be further studied.